2019
DOI: 10.1002/ange.201903684
|View full text |Cite
|
Sign up to set email alerts
|

General Interfacial Self‐Assembly Engineering for Patterning Two‐Dimensional Polymers with Cylindrical Mesopores on Graphene

Abstract: Free-standing 2D porous nanomaterials have attracted considerable interest as ideal candidates of 2D film electrodes for planar energy storage devices.N evertheless,t he construction of well-defined mesopore arrays parallel to the lateral surface,w hichf acilitate fast in-plane ionic diffusion, is achallenge.Now,auniversal interface self-assembly strategy is used for patterning 2D porous polymers,f or example, polypyrrole,p olyaniline,a nd polydopamine,w ith cylindrical mesopores on graphene nanosheets.T he re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…38 After mixing the aqueous solution of the micelles and that of free-standing GO nanosheets, mPD and PA, the hydrogen-bonding and electrostatic interactions among these precursors could drive the close packing of the cylindrical micelles on the surfaces of GO along with the adsorption of mPD and PA in the poly(ethylene oxide) (PEO) domains. [39][40][41] The subsequent polymerization of mPD coupled with the PA doping was confined in the PEO regions, leading to the formation of PA-doped PmPD (PA/PmPD) networks on the GO surfaces. After the removal of the copolymer template, 2D heterostructural nanosheets composed of two mesoporous polymeric PA/PmPD layers with cylindrical pores sandwiching the GO nanosheet are obtained.…”
Section: Resultsmentioning
confidence: 99%
“…38 After mixing the aqueous solution of the micelles and that of free-standing GO nanosheets, mPD and PA, the hydrogen-bonding and electrostatic interactions among these precursors could drive the close packing of the cylindrical micelles on the surfaces of GO along with the adsorption of mPD and PA in the poly(ethylene oxide) (PEO) domains. [39][40][41] The subsequent polymerization of mPD coupled with the PA doping was confined in the PEO regions, leading to the formation of PA-doped PmPD (PA/PmPD) networks on the GO surfaces. After the removal of the copolymer template, 2D heterostructural nanosheets composed of two mesoporous polymeric PA/PmPD layers with cylindrical pores sandwiching the GO nanosheet are obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Mesoporous material (e.g., carbon and metal oxides) on the G sheets can be used as a spacer, which hampers restacking G sheets and provides additional capacitance [ 74 , 82 , 133 , 136 , 143 , 144 , 145 , 146 , 147 ]. Mesoporous carbon/G nanocomposite (mCG) synthesized by KIT-6 had a surface area of 1179 m 2 g −1 and bimodal pores of 3.1 and 3.7 nm [ 74 ].…”
Section: Energy Storage Applicationsmentioning
confidence: 99%
“…Mesoporous metal oxides (e.g., WO 3 , Nb 2 O 5 , TiO 2 ) and G composite can be utilized as an electrode in SC, especially Li- or Na-ion HSCs [ 136 , 144 , 146 ]. The sandwich-structured mesoporous Nb 2 O 5 /G/mesoporous Nb 2 O 5 (G@mNb 2 O 5 ) was used as an anode material in Na-ion HSCs ( Figure 8 D) [ 136 ].…”
Section: Energy Storage Applicationsmentioning
confidence: 99%
“…Apart from the 2D materials discussed above,m any 2D conductingp olymers are also applicable for MSC electrode applications,i ncluding PANI, [36] PPy, [84] and polydopamine (PDA). [23] Generally speaking, 2D polymers have av ariety of merits for electrochemical applications,but face problems of limited electrical conductivity.A ne ffective strategy is to combine them with the materials that have high electrical conductivity.W u et al reported the fabrication of ah ybrid film of thiophene (TP) nanosheets and EG for MSCs( TP/EG MSCs). [21] Benefiting from highly pseudocapacitive TP and highly conductive EG, the TP/EG MSCs delivered an areal capacitance of 3.42 mF cm À2 and av olumetric capacitance of 326 Fcm À3 at 10 mV s À1 .A lso, an impressive rate capability up to 1000 Vs À1 was also achieved.…”
Section: Sandwich-like Stacked Mscsmentioning
confidence: 99%
“…As shown in Figure 1, the configuration of microelectronic devices has developed from linear,p lanar shapes to 3D architectures. [10] At the same time, many materials, such as variouse lementary substances, [11,12] oxides, [13][14][15] sulfides, [16][17][18] hydroxides, [19,20] and organic compounds, [21][22][23] with forms ranging from 0D to 3D, [24][25][26] have been investigatedf or both MB and MSC electrode purposes. Amongt hese, 2D materials attract considerable attention due to their uniquee lectrochemical and mechanical properties when applied in energy storage.…”
Section: Introductionmentioning
confidence: 99%